2022
DOI: 10.1609/aaai.v36i1.19919
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Virtual View Selection for 3D Hand Pose Estimation

Abstract: 3D hand pose estimation from single depth is a fundamental problem in computer vision, and has wide applications. However, the existing methods still can not achieve satisfactory hand pose estimation results due to view variation and occlusion of human hand. In this paper, we propose a new virtual view selection and fusion module for 3D hand pose estimation from single depth. We propose to automatically select multiple virtual viewpoints for pose estimation and fuse the results of all and find this empirically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Early non-parametric models aim at predicting hand joints from depth maps and point clouds (Cheng et al 2022;Deng et al 2022). With the recent advances in network architectures, non-parametric models that predict 3D hand vertices become popular.…”
Section: Non-parametric Hand Modelsmentioning
confidence: 99%
“…Early non-parametric models aim at predicting hand joints from depth maps and point clouds (Cheng et al 2022;Deng et al 2022). With the recent advances in network architectures, non-parametric models that predict 3D hand vertices become popular.…”
Section: Non-parametric Hand Modelsmentioning
confidence: 99%
“…The following works were used HandPE. For 3D hand posture estimate from a single depth, Cheng et al (2022) suggested a virtual view selection and fusion module to solve a HandPE problem through suggesting choosing many virtual perspectives at random, combining the findings, and finding that method empirically produces reliable and accurate pose estimation. They analysed the virtual views based on the confidence of virtual views using a light‐weight network via network distillation to choose the most efficient virtual views for pose fusion.…”
Section: Pose Estimation Typesmentioning
confidence: 99%
“…The estimated poses were then iteratively refined to obtain the final result. In [ 49 ], an approach was proposed that uses a CNN to estimate a 3D hand pose from a single depth image. The method generates multiple viewpoints of the hand, which are then fed to another neural network to estimate hand poses for each viewpoint.…”
Section: Related Researchmentioning
confidence: 99%